THE RELATIONSHIP BETWEEN LEARNING TIME MANAGEMENT, LEARNING MOTIVATION, AND PEER INTERACTION WITH MATHEMATICS LEARNING OUTCOMES - Ria Fridha Kusumaningrum; Uswatun Khasanah (Universitas Ahmad Dahlan, 2019)
Student mathematics learning results are low related to several factors. The correlation between learning time management, learning motivation, and peer interaction are several factors that are likely related to learning results. This study aims to determine whether there is a positive and significant correlation between Learning Time Management, Learning Motivation, and Peer Associations with Mathematics Learning Results of Students at Grade VIII, State Junior High School of 1 Pandanarum (SMP Negeri 1 Pandanarum) in Banjarnegara Regency in the odd semester in the academic year of 2016/2017. This study's population were eighth-grade students of SMP Negeri 1 Pandanarum Banjarnegara Regency in the odd semester in the academic year of 2016/2017, consisting of classes VIII A, VIII B, VIII C, VIII D, VIII E, totaling 145 students. A random sampling technique determined the research sample. Data collection techniques were performed using a questionnaire method to obtain data on learning time management, learning motivation, peer interaction, and test methods to obtain data on mathematics learning results. The research instrument test includes validity tests, different power tests, and reliability tests, while the analysis prerequisite test includes a normality test, linearity test, and independence test. In this study, data analysis was performed using product moment analysis and multiple linear regression analysis. The results showed a positive and significant correlation between learning time management, learning motivation, and peer interaction with mathematics learning results of Grade VIII students of SMP Negeri 1 Pandanarum Banjarnegara Regency in the odd semester the academic year of 2016/2017. This is indicated by Fcount> Ftable which is 8,0123 > 2,9912 with Â R= 0,7001 and R2 = 0,4902 with , with , Â and = 25,1391 , EC Â and .